Overlapping of Serotonin Syndrome with Neuroleptic Malignant Syndrome due to Linezolid-Fluoxetine and Olanzapine-Metoclopramide Interactions: A Case Report of Two Serious Adverse Drug Effects Caused by Medication Reconciliation Failure on Hospital Admission - Faizan Mazhar; Shahzad Akram; Nafis Haider; Rafeeque Ahmed (Case Reports in Medicine)
Antipsychotic and antidepressant are often used in combination for the treatment of neuropsychiatric disorders. The concomitant use of antipsychotic and/or antidepressant with drugs that may interact can lead to rare, life-threatening conditions such as serotonin syndrome and neuroleptic malignant syndrome. We describe a patient who has a history of taking two offending drugs that interact with drugs given during the course of hospital treatment which leads to the development of serotonin syndrome overlapped with neuroleptic malignant syndrome. The physician should be aware that both NMS and SS can appear as overlapping syndrome especially when patients use a combination of both antidepressants and antipsychotics.